2004
DOI: 10.1002/bdd.403
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation phenotype status in a Bangladeshi population and its comparison with that of other Asian population data

Abstract: The objective of the present study was to determine the acetylator status of the Bangladeshi population and to compare the findings with the acetylator status of other Asian populations. The acetylator phenotype was determined in 517 unrelated healthy Bangladeshi subjects. The phenotyping procedure was done according to Price Evans' method using the NAT2 specific probe drug--sulphadimidine. The Bangladeshi population showed a bimodal distribution of fast and slow acetylators. Of a total of 517 healthy Banglade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Acetylator phenotype is a useful predictor of fast and slow acetylators of drugs, and the population differences among fast and slow acetylators have been recognized. In a study of the Bangladesh population (Zaid et al, 2004), it was shown that approximately 67% of the patients (total, 517) fell in the category of fast acetylators of sulfadimidine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetylator phenotype is a useful predictor of fast and slow acetylators of drugs, and the population differences among fast and slow acetylators have been recognized. In a study of the Bangladesh population (Zaid et al, 2004), it was shown that approximately 67% of the patients (total, 517) fell in the category of fast acetylators of sulfadimidine.…”
Section: Discussionmentioning
confidence: 99%
“…Acetylation is a process of phase II conjugation of sulfonamide biotransformation. The genetic variation affects the clinical consequences of being a rapid or slow acetylator (Zaid et al, 2004). The consequences of PG variation in these enzymes include (1) altered kinetics of specific drug substrates, (2) drug-drug interactions resulting from altered kinetics and (3) idiosyncratic adverse drug reactions.…”
Section: Discussionmentioning
confidence: 99%
“…17 Previous work by our laboratory 18 indicated a phenotypic predominance of 74.5% SA in Hmong in contrast to other select Asian populations of geographic proximity in which SA phenotypes range from 6% to 45%. [19][20][21][22][23][24] Consequently, confirming this phenotypic predominance and its basis by correlating metabolic phenotype with NAT2 genotype represents a necessary step before conducting planned epidemiologic studies in the Hmong.…”
mentioning
confidence: 99%
“…Twenty-eight polymorphic variants of the NAT2 gene have been found [12]. The distribution of NAT2 phenotypes has been demonstrated to be associated with geographical latitude [15], the frequency of the fast N-acetylation phenotypes increasing when moving to the equator.Arylalkyl N-acetyl transferase catalyzes the synthesis of melatonin from serotonin in the pineal gland. Melatonin regulates immunity; normalizes sleep; relieves depression; and possess antioxidant, sedative, antiproliferative, and protective properties.…”
mentioning
confidence: 99%
“…Twenty-eight polymorphic variants of the NAT2 gene have been found [12]. The distribution of NAT2 phenotypes has been demonstrated to be associated with geographical latitude [15], the frequency of the fast N-acetylation phenotypes increasing when moving to the equator.…”
mentioning
confidence: 99%